Photophysical and Protonation Time Resolved Studies of Donor-Acceptor Branched Systems With Pyridine Acceptors - Kournoutas, Fotis; Seintis, Kostas; Karakostas, Nikolaos; Tydlitát, Jiří; Achelle, Sylvain; Pistolis, George; Bureš, Filip; Fakis, Mihalis (American Chemical Society, 2019)
A comparative study of the photophysical properties of octupolar pyridyl-terminated triphenylamine molecule, with its quadrupolar and dipolar analogues, by means of ambient and low temperature steady state spectroscopy and femtosecond to nanosecond time-resolved fluorescence spectroscopy is reported. The push-pull molecules bear triphenylamine electron donating core, pyridine peripheral electron acceptors, and acetylene pi-bridge. The samples were studied in solvents of varying polarity and also upon addition of small amounts of acetic acid to induce protonation of the pyridine group. All samples exhibit significant positive fluorescence solvatochromism as well as a relaxation of their excited state to a solvent relaxed intramolecular charge transfer state on the picosecond time scale. For the octupolar compound, excited state relaxation occurs simultaneously with excitation energy hopping among the branches. The hopping time is solvent polarity controlled since it becomes slower as the polarity increases. The experimental hopping times are compared to those predicted by Forster and Fermi formulations. The samples are capable of emitting broadband light covering almost the whole visible spectrum by careful control of protonation. Energy transfer from the neutral toward the protonated species on the 1 ps time scale is revealed.
Fotofyzikální a protonační time-resolved studie donor-akceptorového rozvětveného systému s pyridinovými akceptory
Keywords: excitation-energy transfer; excited-state dynamics; intramolecular charge-transfer; nonlinear-optical properties; white-light emission; 2-photon absorption; triphenylamine derivatives; fluorescence; chromophores; dipolar; pyridin; trifenylamin; time-resolved fluerescence